Maximal aerobic speed as a useful tool to understand specific training demand among elite male volleyball - Zerf, Mohammed; Louglaib, Lakhdar (Pedagogy and Psychology of Sport, 2019)
Aim: The study aims to study the impact of Maximal Aerobic Speed (MAS) levels on the growth of skills fitness among volleyball. Methods: To achieve this objective, we assess the levels of MAS for 60 elite male volleyball players (ages 22 to 25 years with +5 years' experience in elite championships). Tested by volleyball Alberta tests and standing triple jump and T agility tests to estimate the effect of coordination abilities on players body adaptations to recover from the highintensity and fatiguing actions as a result of levels of endurance. Results: Backup on statistics applied, centred on MAS levels as protocol. We confirmed that a high-level of MAS enhanced skills fitness. Admitted by the inverse correlation between the levels of MAS in compares with speed, power and explosive abilities. In the benefits of players with elevated levels of MAS as a beneficial condition to improve skills fitness (Serve-attack/Spike/Block) among volleyball players. Conclusion: our protocol supports the development of MAS at 4 + (m/s). Agreed as minimal components of physical condition allied to neuromuscular system adaptations, which permit players not only to improve their speed and power components. But also, their ability to recover from highintensity and fatiguing actions.
Keywords: maximal aerobic speed; volleyball; elite; skill physically ability; correlation